Functional chitosan/zein films with Rosa roxburghii Tratt leaves extracts prepared by natural deep eutectic solvents. (December 2022) - Zhao, Pengquan; Wang, Jiandong; Yan, Xinyu; Cai, Zihui; Fu, Lina; Gu, Qi; Liu, Lin; Jin, Haojie; Fu, Yujie
Abstract: In this study, the bioactive extract of Rosa roxburghii Tratt (RRT) leaves was incorporated into a chitosan/zein matrix to produce a food packaging film with higher antioxidant and antimicrobial activities. The natural deep eutectic solvent (NADES) was taken as the extraction solvent and green plasticizer to prepare the film matrix. The physical and structural properties of chitosan/zein films with different concentrations of RRT leaves extracts were characterized by infrared spectroscopy analysis, thermogravimetric analysis, X-ray diffraction and scanning electron microscope. The incorporation of RRT leaves extract significantly improved the mechanical properties, light barrier properties and water vapor permeability of the chitosan/zein films. Moreover, the films containing RRT leaves extract had better antioxidant activities and antibacterial activities, with the highest DPPH and ABTS radical scavenging activities of 88.17 % and 86.84 %, respectively, and also effectively inhibited the growth of microorganisms and extended the shelf life of blueberries and cherry tomatoes. Graphical Abstract: ga1 Highlights: A chitosan/zein active packaging film containing Rosa roxburghii Tratt (RRT) leaves extract was developed. Natural deep eutectic solvents could be used directly as extractants and plasticizers. Chitosan/zein films containing RRT leaves extract had higher tensile strength，light barrier property and bioactivity. Chitosan/zein films containing RRT leaves extract effectively extended the shelf life of blueberries and cherry tomatoes.